Low voltage ride-through strategies for doubly fed induction machine pumped storage system under grid faults. (September 2016) - Damdoum, Amel; Slama-Belkhodja, Ilhem; Pietrzak-David, Maria; Debbou, Mustapha
Abstract: Pumped storage units bring stability to the electrical power system, so they must remain connected to the grid even during grid faults. In this paper, the authors propose efficient and simple solutions for a doubly fed induction machine pumped storage (DFIMPS) system during grid faults. In case of balanced grid faults, a control reconfiguration strategy is introduced and a hardware solution is applied in the case of unbalanced grid faults. The reconfiguration strategy consists of a commutation between different control strategies; when a balanced grid voltage fault occurs during pumping mode, the control algorithm switches to the synchronization one but based on the new grid conditions. So the proposed reconfiguration method reduces the negative impacts of grid fault occurrence on the DFIMPS system by cancelling rotor and stator over-currents and decreasing the electromagnetic torque and stator power oscillations. Simulation results carried out on a 4 kW DFIMPS system illustrate the effectiveness of the proposed approach. Highlights: The control strategies of DFIM pumped storage system are detailed. New simple Fault Ride Through (FRT) Strategies for grid faults are proposed. For balanced faults, FRT strategy consists to adjust the DFIM speed and to switch to the control of an intermediate phase. For unbalanced faults, the FRT is realized through three-phase asymmetrical Damping Resistor.